An Archaeological Perception on the Evolving Art of Chinese Calligraphy: Social and Cultural Significance - Boqianshi Zhang (Art and Society, 2024)
Chinese calligraphy is a significant aspect of Chinese culture, showcasing the evolution of Chinese writing and exemplifying the pinnacle of Chinese art. This art represents a nation’s creativity and holds significant archaeological data. This paper will examine the significance of Chinese calligraphy through an analysis of the evolution of Chinese writing, writing instruments, and the utilization of archaeology in calligraphy studies.